Pre-Clinical Laboratory Evaluation of Chlorhexidine for Disinfection of Semi-Critical Respiratory Equipment in Nursing Practice - Ariningpraja, Rustiana Tasya; Ulfa, Marina; Jayadi, Lukky; Maslukha, Andini; Effendy, Nuraeni (Chakra Brahmanda Lentera Institute, 2026)
Background: Healthcare-associated infections (HAIs) remain a persistent challenge in nursing practice, particularly in the reprocessing of semi-critical respiratory equipment. Although chlorhexidine is widely used as an antiseptic, evidence regarding its pre-clinical disinfectant performance, physicochemical suitability, and waste safety within nurse-led device reprocessing workflows remains limited. This gap is especially relevant in settings where reusable respiratory devices are routinely handled by nurses. Methods: This study employed a pre-clinical experimental laboratory design. The independent variable was chlorhexidine concentration, while dependent variables included antimicrobial efficacy (phenol coefficient), physicochemical parameters (pH, specific gravity, viscosity), and acute toxicity. Antimicrobial testing was conducted against Staphylococcus aureus and Pseudomonas aeruginosa. Physicochemical assessments followed standardized laboratory procedures, and acute toxicity was evaluated using Danio rerio (zebrafish) larvae to inform waste disposal safety. Expert validation was conducted using the Content Validity Index (CVI). Descriptive and endpoint-based analyses were applied without inferential statistics. Results: Chlorhexidine demonstrated strong bactericidal activity against both test organisms, with phenol coefficient values indicating effective disinfectant performance. Physicochemical characteristics remained within acceptable ranges for semi-critical respiratory device reprocessing. Toxicity assessment showed dose-dependent larval mortality, indicating the need for dilution before waste discharge. Expert validation identified chlorhexidine 7.5% as the most clinically relevant concentration for nurse-led practice. No p-values were applied due to the endpoint-based experimental design. Conclusion: Chlorhexidine shows effective pre-clinical disinfectant potential for semi-critical respiratory equipment within controlled laboratory conditions. Its application in nursing practice should be accompanied by standardized concentration control and mandatory dilution before disposal to mitigate environmental toxicity. Further clinical and field-based validation is recommended.